2015
DOI: 10.1099/ijsem.0.000458
|View full text |Cite
|
Sign up to set email alerts
|

Aquabacterium olei sp. nov., an oil-degrading bacterium isolated from oil-contaminated soil

Abstract: T is a Gram-negative, motile, non-spore-forming bacterium isolated from oilcontaminated soil in South Korea. The strain was able to grow by using gasoline, diesel and kerosene as energy and carbon sources. After incubation for 14 days, cells (1 g l 21) degraded approximately 58 % of oil present at concentration of 1500 p.p.m. at pH 8 and 28 8C. Strain NHI-1 T grew well under aerobic conditions, with optimal growth at pH 7-9 and 28 8C-37 8Cbut grew poorly in the presence of ¢0.5 % NaCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…S4). The predominant and known polar lipids were PE, PG, PS and DPG consistent with previous descriptions of species of Aquabacterium [3–5].…”
Section: Chemotaxonomysupporting
confidence: 88%
See 2 more Smart Citations
“…S4). The predominant and known polar lipids were PE, PG, PS and DPG consistent with previous descriptions of species of Aquabacterium [3–5].…”
Section: Chemotaxonomysupporting
confidence: 88%
“…limnoticum , isolated from spring water in Taiwan [2, 3], A. olei , isolated from oil-contaminated soil in Korea [4] and A. tepidiphilum , isolated from hot spring in China [5].…”
Section: Full-textmentioning
confidence: 99%
See 1 more Smart Citation
“…Burkholderiales possess a broad range of enzymes able to degrade polyaromatic hydrocarbons (PAHs), which include important soil pollutants (Pérez-Pantoja et al, 2012). Aquabacterium was first isolated from biofilms of a drinking water system (Kalmbach et al, 1999), and a species of the genus was shown to degrade oil (Pham et al, 2015). Strains of the genus Variovorax hold highly diverse catabolic capabilities, including the degradation of 3,3'-Thiodipropionic acid (TDP), an additive widely used to stabilize polymers, as well as dimethyl terephthalate and vinyl chloride, two other chemicals used in plastic production (Satola et al, 2013;Wilson et al, 2016).…”
Section: Bacterial Key Taxa Associated With Plasticsmentioning
confidence: 99%
“…Brachymonas was able to degrade PAHs [38], and Treponema was the dominant strain during the pentachlorophenol dechlorination with acetate [39]. Aquabacterium was found to degrade oil [40], benzene [41], and methyl tert -butyl ether (MTBE) [42], while Bacteroides could degrade MTBE [43]. These genera could play important roles in the biodegradation process of EDB.…”
Section: Resultsmentioning
confidence: 99%